Redefining social support : a scoping review of the effects of digital technologies on the social support of older workers - Tofan, Cristina Maria; Ševčíková, Anna; Yaylagul, Nilufer Korkmaz; Kulla, Gunilla; Yıldızer, Günay; Mercan, Murat Anil; Barlın, Hande; Gu, Yang; Nilsson, Kerstin ; 0000-0002-3193-205X; Grad, Diana Alecsandra; Gomes, João Rocha; Spijker, Jeroen (BMC Public Health, 2026)
INTRODUCTION: The rapid digitalisation of workplaces presents both challenges and opportunities for older workers. This scoping review examines how digital technologies impact social support for older workers, focusing on emotional, informational, and instrumental support within professional environments. While social support is critical for well-being and productivity in ageing workforces, the effects of digitalisation on social support dynamics remain insufficiently understood. METHODS: Following Joanna Briggs Institute and PRISMA-ScR guidelines, a comprehensive search strategy was conducted across databases like ERIH, Web of Science, Scopus, and PubMed from anytime to 2023 to identify peer-reviewed studies involving digital technologies used by older workers, generally considered as workers aged 50 years or older. Covidence software facilitated the screening of over 5000 scientific papers, study selection, and data extraction, and the Mixed Methods Appraisal Tool (MMAT) assessed quality. Findings were synthesized through descriptive statistics and narrative analysis. RESULTS: Forty-three studies met inclusion criteria. Digital technologies were found to enhance various forms of social support: remote work tools, messaging apps, and telemedicine platforms facilitated emotional connection and informational exchange. However, digitalisation also introduced barriers, some older workers reported isolation, reduced informal contact, and technostress, underscoring disparities in digital literacy and adaptation. DISCUSSION: Digitalisation exerts a dual impact on social support for older workers: it can strengthen professional connectedness yet also heighten vulnerability to stress and exclusion. Targeted digital literacy initiatives and sustained managerial engagement are crucial to ensure that technology enhances, rather than undermines, well-being and productivity among ageing employees.
© 2026. The Author(s).